2011
DOI: 10.1189/jlb.0410231
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamics and differential infection profiles of lymphoid and myeloid cell subsets during acute and chronic HIV-1 infection

Abstract: The dynamics of immune cell populations during acute HIV-1 infection are not fully deciphered, especially for non-T cells. In this study, we tested whether specific cellular subsets of the innate arm of the immune response are affected early after HIV-1 infection. Using a cohort of HIV-1-infected individuals, we have monitored the relative frequency of blood T lymphocytes, monocytes, and DCs at various infection stages and measured their respective intracellular HIV-1 DNA loads. The HIV-1 DNA load in naive CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Although most HIV particles are rapidly degraded upon their encounter with a DC (34,35), providing material for MHC-II Ag presentation (32,36,37), some viral particles escape degradation and are either directly transmitted to CD4 + T cells by trans-infection or initiate cis-infection of DC. Indeed, in the absence of treatment, infected DC can be found in the blood of HIV + donors (38)(39)(40) and, ex vivo, sorted BCDA1 + myeloid DC support productive infection of HIV-1 (41,42). Monocyte-derived DC are also equipped with HIV receptors (CD4, CCR5, and CXCR4) allowing cis-infection (35,(43)(44)(45).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…Although most HIV particles are rapidly degraded upon their encounter with a DC (34,35), providing material for MHC-II Ag presentation (32,36,37), some viral particles escape degradation and are either directly transmitted to CD4 + T cells by trans-infection or initiate cis-infection of DC. Indeed, in the absence of treatment, infected DC can be found in the blood of HIV + donors (38)(39)(40) and, ex vivo, sorted BCDA1 + myeloid DC support productive infection of HIV-1 (41,42). Monocyte-derived DC are also equipped with HIV receptors (CD4, CCR5, and CXCR4) allowing cis-infection (35,(43)(44)(45).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…This finding indicates that quantification of viral DNA alone is not necessarily predictive of the size of the inducible latent reservoir and suggests caution in labeling a cellular reservoir of latent HIV-1 as "major" based solely on the frequency of infection. In addition to the memory CD4 ϩ T cell subsets, HIV-1 DNA is almost always detected in T N cells in both viremic and suppressed individuals, although with a much lower frequency than in the T CM and T TM compartments (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Interestingly, in 2013 Saez-Cirion et al reported that in some HIV-1-infected individuals who received ART within 10 weeks of primary infection, viremia could be controlled for at least 24 months posttreatment interruption (8).…”
Section: A Latent Hiv-1 Reservoir Is Established In Resting Cd4mentioning
confidence: 99%
“…Of all the tested variables, only nadir CD4 þ showed a significant (negative) correlation to CA-US HIV-1 RNA (r ¼ À0.465, P ¼ 0.017) which could reflect a functional defect in the cellular immune response in individuals with low nadir CD4 þ due to lack of immunological recovery. Since the latently infected cells are mainly within the CD4 þ T-memory subsets and the proportions of naive CD4 þ T cells vs. memory CD4 þ T cells varies between HIV-infected individuals, we adjusted all measures for the proportion of naïve T cells [12,[54][55][56][57]. This correlation remained significant when adjusted for the relative contribution of T N at baseline (r ¼ À0.477, P ¼ 0.014).…”
Section: Study Populationmentioning
confidence: 99%